Analyzing the incidence, survival, and demographic trends of B-cell prolymphocytic leukemia - Nnawuba, Kingsley; Uche, Ifeanyi; Robinson, Samantha; Asare, Obed; Nzeako, Tochukwu; Trikannad Ashwini Kumar, Anup Kumar; Jensen, Hanna (International Journal Of Community Medicine And Public Health, 2024)
Background: B-cell prolymphocytic leukemia (B-PLL) is a rare disease, consisting <1% of mature B-cell malignancies. B-PLL is often refractory to chemotherapy, with a median survival of 3 years. Due to its rarity, no large cohort studies exist elucidating outcomes. Methods: All B-PLL patients >15 years were identified in the National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) database between 2000-2020. Statistical analysis explored demographic variables like age; categorized as adolescent or young adult (AYA) and adults. In adults, differences in survival due to factors such as sex, race/ethnicity, household income, rurality, and age categorized in 10-15 year buckets was analyzed. Results: B-PLL patients were predominantly white (78%), over 40 years (96%) and mostly residing in metropolitan areas (90%). Interestingly, the AYA cohort were mostly female (70%). 35% of the AYA patients were Hispanic, while being only 9% in adults. Among adults, the rate of Asian/Pacific-Islander patients that were alive at the time of the data query was 53% compared to 34% in Hispanic, 31% in black, and 24% in white patients (p=0.025). Younger age was also associated with greater chances of survival (p<0.001). Conclusions: In line with known poor prognosis of the disease, 23% patients were alive at the time of data query. Female and Hispanic patients were overrepresented in the AYA age group. In the adult group Asian/Pacific-Islander patients had better survival outcomes, as did younger patients. Further research is necessary to explore why B-PLL incidence in AYA patients is higher among Hispanic and females.